Evaluation of mechanical properties for open cellular structure 17-4 PH stainless steel alloy fabricated by selective laser melting process - M. F. F. A., Hamidi; W. S., Wan Harun (Centre for Advanced Research on Energy (CARe), 2017)
Additive layer manufacturing processestechnology especially selective laser melting process has offered capabilities to produce samples with excellent mechanical properties. In this study, samples of 17-4 PH Stainless Steell open cellular structure with variousvolume porosity ranging between 60% and '90% has. been fabricated using direct metal laser sintering process. The mechanical properties were determined through uniaxial compression and hardness testing. The 60% volume porosily samplet showel the optimum compressive strength and modulus of elasticity compared to 70%, 80% and 90% volume porosity for [he compression test. For hardness test. the different Surfuce area seerns does not affect the hardness value of the samples